2013
DOI: 10.1242/dev.090423
|View full text |Cite
|
Sign up to set email alerts
|

Bithorax-complex genes sculpt the pattern of leucokinergic neurons in theDrosophilacentral nervous system

Abstract: SUMMARYAlthough the Hox genes are the main factors involved in the generation of diversity along the anterior/posterior body axis of segmented organisms, it is still largely unknown how these genes act in single cells to determine specific traits at precise developmental stages. The aim of this study was to understand the mechanisms by which Hox genes of the Bithorax complex (Bx-C) of Drosophila act to define segmental differences in the ventral nerve cord of the central nervous system. To achieve this, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 75 publications
0
40
0
Order By: Relevance
“…1D, E). During pupal development a set of 8 additional LK neurons appear anteriorly in the abdominal ganglia [37], [39]; these have far larger cell bodies than the 14 posterior ABLKs (Fig. 1D, E).…”
Section: Resultsmentioning
confidence: 99%
“…1D, E). During pupal development a set of 8 additional LK neurons appear anteriorly in the abdominal ganglia [37], [39]; these have far larger cell bodies than the 14 posterior ABLKs (Fig. 1D, E).…”
Section: Resultsmentioning
confidence: 99%
“…Much of our current understanding of how Hox genes impact neuronal development comes from studies on mouse MNs in the hindbrain and spinal cord, as well as leg MNs, neuroblasts and peptidergic ventral nerve cord neurons in Drosophila (Baek et al, 2013; Catela et al, 2016; Estacio-Gómez and Díaz-Benjumea, 2014; Estacio-Gómez et al, 2013; Karlsson et al, 2010; Mendelsohn et al, 2017; Miguel-Aliaga and Thor, 2004; Moris-Sanz et al, 2015; Philippidou and Dasen, 2013; Suska et al, 2011). In C. elegans , Hox genes have also been recently shown to diversify touch receptor neuron identity (Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…1C). 21 ABLKs are generated during embryonic neurogenesis by NB5-5 in the first to the seventh abdominal segments of the VNC, producing a fixed number of 7 ABLKs per hemiganglion (embryonic ABLKs: eABLKs). 37 We observed that the number of ABLKs increased during pupal stages, reaching an average of 11 in 4-day-old adults.…”
Section: Actions Of Hox Genes In Controlling Segment Diversity Througmentioning
confidence: 99%
“…39 Similar variability can be observed in the number of postembryonic neurons that produce neuropeptides, for instance, in the number of neurons producing the neuropeptide leucokinin or bursicon in the adult fly. 21,40 Thus, the number of Lk-expressing neurons in the adult CNS varies depending on the environmental conditions and on the number of copies of Abd-B. This has led us to suggest that the level of expression of Abd-B might be affected by the environmental conditions of the larva and so control the number of neurons that produce leukoquinin.…”
Section: Role Of Abd-b As a Sensor Of The Enviromental Conditions Of mentioning
confidence: 99%
See 1 more Smart Citation